Efficacy of Daratumumab-Containing Regimens Among Patients With Multiple Myeloma Progressing on Lenalidomide Maintenance: Retrospective Analysis - Mian, Hira; Eisfeld, Christine; Venner, Christopher P.; Masih-Khan, Esther; Kardjadj, Moustafa; Jimenez-Zepeda, Victor H.; Khandanpour, Cyrus; Lenz, Georg; McCurdy, Arleigh; Sebag, Michael; Song, Kevin; LeBlanc, Richard; et al. (Frontiers in Oncology, 2022)
Background: Daratumumab, a monoclonal antibody directed against CD38 is a recent class of drugs introduced into the multiple myeloma therapeutic landscape. While clinical trial data has shown a remarkable impact on outcomes, the efficacy of daratumumab combination therapies in specific clinically relevant subgroups including among patients refractory to lenalidomide maintenance remains unknown. Methods: In this study, retrospective data was reviewed from the Canadian Myeloma Research Group and the German Munster Myeloma databases to identify patients that received daratumumab in combination with pomalidomide (DPd), lenalidomide (DRd) and bortezomib (DVd) in a population that had relapsed on lenalidomide maintenance post autologous stem cell transplant. The primary aim of the study was to look at outcomes of these patients in different daratumumab combinations. Results: A total of 73 patients were identified. The median age of the patients at the time of daratumumab initiation was 60 (38-72) and 64.4% (n=47) were males. In the selected cohort, 43.8% (n=32) were treated with DRd, 31.5% (n=23) with DVd and 24.7% (n=18) with DPd regimen. The median PFS of the entire cohort was 15.8 months (95% CI 12.9-37.1 months). The median PFS of the individual regimens was as follows: DPd 18.9 months (95% CI 13.7-not reached), DRd 21.7 months (95% CI 11.6-not reached) and DVd 12.9 months (95% CI 3.1-not reached). Conclusions: Daratumumab containing therapies especially those in combination with immunomodulatory agents are effective regimen in patients progressing on lenalidomide maintenance. Additional studies are required to decide the optimal regimen post lenalidomide maintenance.